2007
DOI: 10.1038/sj.emboj.7601682
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism for activation of the growth factor-activated AGC kinases by turn motif phosphorylation

Abstract: The growth factor/insulin-stimulated AGC kinases share an activation mechanism based on three phosphorylation sites. Of these, only the role of the activation loop phosphate in the kinase domain and the hydrophobic motif (HM) phosphate in a C-terminal tail region are well characterized. We investigated the role of the third, socalled turn motif phosphate, also located in the tail, in the AGC kinases PKB, S6K, RSK, MSK, PRK and PKC. We report cooperative action of the HM phosphate and the turn motif phosphate, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
109
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 100 publications
(120 citation statements)
references
References 32 publications
7
109
0
Order By: Relevance
“…10 of the enzyme [28,29,50]. While phosphorylation at the TM influences enzyme stability, differences have been reported as to the importance of this site for catalytic activity (Table 1).…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
See 3 more Smart Citations
“…10 of the enzyme [28,29,50]. While phosphorylation at the TM influences enzyme stability, differences have been reported as to the importance of this site for catalytic activity (Table 1).…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…While phosphorylation at the TM influences enzyme stability, differences have been reported as to the importance of this site for catalytic activity (Table 1). For example, phosphorylation at the TM is required for PKC I and PKC II activity [51,52], while it is dispensable for PKC , PKC and PKC activity [53,31,50]. In contrast, conflicting results have been reported as to importance of TM phosphorylation for PKC activity [54,55] and PKC activity [56,50].…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
See 2 more Smart Citations
“…This Thr residue is constitutively phosphorylated in the absence of extracellular stimuli (Alessi et al, 1996), depending on mTORC2 (Facchinetti et al, 2008;Ikenoue et al, 2008). Structural studies have suggested that this modification contributes to the correct conformation of Akt (Hauge et al, 2007). Early Akt activation studies showed that TM phosphorylation is not essential for phosphorylation of the other sites (Toker and Newton, 2000); however, considering the emerging complexity of the Akt activation mechanism, such as the discrepancy over the mutual dependency of A-loop and HM phosphorylation, the involvement of TM phosphorylation in the phosphorylation of the A-loop and/or the HM needs to be re-evaluated.…”
Section: Introductionmentioning
confidence: 99%